(untitled) (Journal of Applied Oral Science, 2022)
Objective: Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) is a member of the carcinoembryonic antigen family. Although its expression has been found in chronic oral inflammatory epithelium, this study aimed to know whether CEACAM1 in oral keratinocytes participates in host immune response against Candida albicans . Methodology: We investigated CEACAM1 expression in oral keratinocytes induced by C. albicans as well as by Candida cell wall component β-glucan particles (β-GPs). Furthermore, the effects of CEACAM1 on β-GPs-induced heme oxygenase-1 (HO-1) expression and its related signals were examined. Results: Fluorescence staining showed CEACAM1 expression in oral keratinocytes (RT7) cells, whereas quantitative reverse transcription (RT)-PCR indicated that both live and heat-killed C. albicans increased CEACAM1 mRNA expression in RT7 cells. Examinations using quantitative RT-PCR and western blotting indicated that CEACAM1 expression was also increased by β-GPs derived from C. albicans . Specific siRNA for CEACAM1 decreased HO-1 expression induced by β-GPs from C. albicans as well as the budding yeast microorganism Saccharomyces cerevisiae . Moreover, knockdown of CEACAM1 decreased β-GPs-induced ROS activity in the early phase and translocation of Nrf2 into the nucleus. Conclusion: CEACAM1 in oral keratinocytes may have a critical role in regulation of HO-1 for host immune defense during Candida infection.